Reading "Chishanga" in the colonial archive: some Issues of process and method - Mazarire, Gerald C. (National Archives of Zimbabwe, 2016)
Growing up on a farm in the Mshawasha African Purchase Area some twenty kilometres south of Great Zimbabwe in the Masvingo Province, south-central Zimbabwe, I had often heard elders refer to the area colloquially as „Chishanga‟. This name seemed expansive because it could also be applied to the nearby areas such as the modern Ngomahuru Hospital complex and surrounding areas, yet even Chief Mapanzure, in the neighbouring communal area, was said to rule this Chishanga territory. Certainly this commonality of belonging could be confirmed by networks of kinship in these seemingly varied spaces which sounded old and established. There was a point however, where Chishanga seemed to end, almost abruptly, but those making the distinction between those spaces that were no longer Chishanga and those that still were, seemed so sure.